Dust Storm Assessment in the Southwest of Afghanistan - Shirzad, Mohammad Dawod (Journal of Natural Sciences – Kabul University, 2021)
Small-scale pressure variations play a critical role in generating the strong “wind of 120 days” that frequently occurs in western Afghanistan. The Weather Research and Forecasting with Chemistry (WRF/Chem) model, alongside existing interpretations, was used to examine this wind phenomenon, dust storm activity over the Helmand Basin, and key sources of dust affecting Afghanistan and Balochistan. These winds are prevalent from mid-May to mid-September due to persistent high-pressure systems over the Hindu Kush mountains in northern Afghanistan, combined with a summertime thermal low over western Afghanistan’s desert lands. The resultant pressure gradient intensifies winds, which are further channeled by the region’s orography. A northerly low-level jet (LLJ) along the Afghanistan-Iran border peaks at 300–500 meters altitude and is most intense in July, with nighttime monthly averaged wind speeds reaching 20 m/s, spreading across a broad latitudinal area along the border.